Transient, flexible gene editing in zebrafish neutrophils and macrophages for determination of cell-autonomous functions - Abdulsalam I. Isiaku; Zuobing Zhang; Vahid Pazhakh; Harriet R. Manley; Ella R. Thompson; Lucy C. Fox; Satwica Yerneni; Piers Blombery; Graham J. Lieschke (The Company of Biologists, 2021)
Zebrafish are an important model for studying phagocyte function, but rigorous experimental systems to distinguish whether phagocyte-dependent effects are neutrophil or macrophage specific have been lacking. We have developed and validated transgenic lines that enable superior demonstration of cell-autonomous neutrophil and macrophage genetic requirements. We coupled well-characterized neutrophil- and macrophage-specific Gal4 driver lines with UAS:Cas9 transgenes for selective expression of Cas9 in either neutrophils or macrophages. Efficient gene editing, confirmed by both Sanger and next-generation sequencing, occurred in both lineages following microinjection of efficacious synthetic guide RNAs into zebrafish embryos. In proof-of-principle experiments, we demonstrated molecular and/or functional evidence of on-target gene editing for several genes (mCherry, lamin B receptor, trim33) in either neutrophils or macrophages as intended. These new UAS:Cas9 tools provide an improved resource for assessing individual contributions of neutrophil- and macrophage-expressed genes to the many physiological processes and diseases modelled in zebrafish. Furthermore, this gene-editing functionality can be exploited in any cell lineage for which a lineage-specific Gal4 driver is available. This article has an associated First Person interview with the first author of the paper.